Theological Education as Practice of Hospitality - Behera, Marina Ngursangzeli (Transformation, 2023)
This article will explore the metaphor of hospitality as an approach to theological education and missional formation for bridging the gap between the catholicity of the church and theological curricula which are rooted in specific traditions and contexts. The argument starts with a reflection on online teaching as a context renewed through the pandemic which reflects back on classroom teaching. The article explores the forms of presence offline and online and fleshes out what hospitality offers for new avenues for theological education and missional formation in context.